Development of Science Process Skills Assessment Instrument in Physics Learning at Dr.Wahidin Sudirohusodo Junior High School Medan - Apriani Sijabat; Palma Juanta; Festiyed Festiyed (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to produce a valid and reliable Science Process Skills (KPS) assessment instrument in learning Physics temperature and heat material. The research is a Research and Development study with the ADDIE model. The research was conducted at Dr. Wahidin Sudirohusodo Junior High School in Medan. The sample in the study came from 2 physics education lecturers and 3 physics teachers. The instruments in this study were a 15-item multiple choice KPS test sheet and a validation questionnaire. Data collection techniques in the form of tests and validation questionnaires. The KPS indicators studied were observing, formulating hypotheses, identifying variables, interpreting data, communicating, and applying concepts. Data analysis is quantitative and qualitative data analysis with the help of the SPSS version 21 application. The results validation value of 34%, language validation of 31% and validation of 35% with decent criteria, reliability of 0.862 high criteria. This finding explains that the KPS instrument is very valid and reliable to be used in learning physics temperature and heat material.